2022
DOI: 10.21037/jtd-21-1512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hospital case volume on clinical outcomes of patients requiring extracorporeal membrane oxygenation: a territory-wide longitudinal observational study

Abstract: Background: The utilization of extracorporeal membrane oxygenation (ECMO) has increased rapidly around the world. Being an overall low-volume high-cost form of therapy, the effectiveness of having care delivered in segregated units across a geographical locality is debatable.Methods: All adult extracorporeal membrane oxygenation cases admitted to public hospitals in Hong Kong between 2010 and 2019 were included. "High-volume" centers were defined as those with >20 extracorporeal membrane oxygenation cases in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Barbaro et al demonstrated that the annual extracorporeal membrane oxygenation (ECMO) patient volume has a potential impact on case-mix-adjusted hospital mortality rate for patients supported by ECMO [3]. However, a recent paper challenged this observation and did not show an associated between the hospital volume and the ECMO outcome [82]. ECMO is resource intensive technology and that might limit its use [83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barbaro et al demonstrated that the annual extracorporeal membrane oxygenation (ECMO) patient volume has a potential impact on case-mix-adjusted hospital mortality rate for patients supported by ECMO [3]. However, a recent paper challenged this observation and did not show an associated between the hospital volume and the ECMO outcome [82]. ECMO is resource intensive technology and that might limit its use [83].…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent studies from the extracorporeal life support organization (ELSO) showed that the use of V-V ECMO in COVID-19 is associated with an in-hospital mortality of 36.9-51.9% at 90 days [80,81]. Similarly, in a French retrospective single healthcare system analysis, the estimated probability of death at 60 days post-ECMO initiation was 31% [82]. Most recently, in a comparative analysis of COVID Critical Care Consortium, the use of V-V ECMO in comparison to mechanical ventilation only was associated with a significantly reduced mortality especially in patients less than 65 years old and with a PaO 2 /FiO 2 < 80 mm Hg or with driving pressures >15 cmH2O during the first 10 days of mechanical ventilation [83].…”
Section: Extracorporeal Membrane Oxygenation During Coronavirus 2019 ...mentioning
confidence: 99%
“…The current clinical scenario pushes every cardiac surgery unit to provide an ECLS service besides the normal cardiac surgery activity, regardless of the center's ECLS case load. Nevertheless, to optimize outcomes, it is recommended that centers performing ECLS for cardiac failure achieve a minimum ECLS volume of 30 cases per year, with a substantial proportion being for cardiac failure 11,12,13,15 . This survey revealed that several hospitals providing V‐A ECLS for post‐cardiotomy shock perform ≤30 V‐A ECLS cases per year, and these low‐volume centers are mainly non‐academic.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to optimize outcomes, it is recommended that centers performing ECLS for cardiac failure achieve a minimum ECLS volume of 30 cases per year, with a substantial proportion being for cardiac failure. 11,12,13,15 This survey revealed that several hospitals providing V-A ECLS for post-cardiotomy shock perform ≤30 V-A ECLS cases per year, and these low-volume centers are mainly non-academic. Both low-volume and high-volume centers seem to be aligned on several clinical practices, including access to other mechanical circulatory support devices or the presence of ECLS specialists.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of AJTCCM , Van Zijl et al [13] retrospectively report the outcomes of all patients supported with VV- and VA-ECMO at Netcare Milpark Hospital, a high-volume centre (defined as >20 cases per year [14] ) in Johannesburg, SA, that treated 107 patients over >2 years during a period predating the COVID pandemic. Most patients (73%) had respiratory failure as their indication for ECMO, with 54% of the cohort receiving VV-ECMO.…”
Section: Editorialmentioning
confidence: 99%